Pemanfaatan Silent Reflection Berbasis Nilai Tafakur dalam Pembelajaran PAI untuk Meningkatkan Kesadaran Spiritual Siswa di Sekolah MA al-Amin - Ahmad Hafis Taufiqi; M. Firmansyah (ALSYS, 2026)
The low spiritual awareness of students in Islamic Religious Education (PAI) learning, which tends to be cognitively oriented, indicates the need for a learning approach that can internalize spiritual values more deeply. This study aims to analyze the use of silent reflection based on the value of tafakur in improving students’ spiritual awareness at MA Al-Amin. This study used a qualitative approach with a case study design. The research subjects included PAI teachers and students, with data collected through observation, interviews, and documentation. The results showed that the implementation of tafakur-based silent reflection was able to create a reflective learning atmosphere, increase students’ self-awareness of divine values, and strengthen their spiritual relationship with Allah SWT. In addition, students showed changes in attitudes, including increased calmness, sincerity, and awareness in worship. Thus, tafakur-based silent reflection is effective as a PAI learning strategy that integrates cognitive and affective aspects. The implications of this study emphasize the importance of developing a spiritual reflection-based learning model as an innovation in Islamic education to sustainably shape students’ religious character.